Faktor Determinan yang berhubungan dengan Penanganan Program Tuberkulosis (TB) di Lombok Tengah - Saimi Saimi; Nanang Kosim; Lalu Abdul Khalik; Dita Retno Pratiwi (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, mainly attacking the lungs, but can affect other organs. The disease remains a significant global and national health problem, including one of the world's top 10 causes of death and the deadliest infectious disease. TB cases in Central Lombok in 2022–2024 fluctuated, rising from 1,220 to 1,538 and then dropping to 1,467 cases. Pediatric TB increased significantly, the success of therapy increased, but the rate of dropouts, failed treatment was high, and mortality also increased. The main potential barriers include low knowledge, stigma, poor access to services, and limited facilities, these conditions underscore the urgency of research on national TB elimination strategies. Purpose: to analyze determinant factors related to the Handling of the Tuberculosis (TB) Program in Central Lombok. Result: It was found that patient knowledge, access to TB services, social stigma, and medication adherence had a significant effect on the success of TB treatment (p < 0.005). Patients with low knowledge were at risk of 3.97 times of barriers, of difficulty of access increased risk 7.23 times, of stigma 8.13 times, and of low adherence 4.54 times. These findings underscore the need for TB control strategies that prioritize patient education, improved access to services, reduced social stigma, and support for ongoing treatment adherence to improve the success of TB programs. Conclusion: This study shows that successful TB treatment is significantly influenced by patient knowledge, access to services, social stigma, and medication adherence. The risk of treatment barriers increased nearly four times in low-knowledge patients, more than seven times in difficult access, and eight times in high-stigma. Low drug adherence also has a significant impact. TB control strategies must prioritize education, increased access, stigma reduction, and patient compliance assistance on an ongoing basis.